2021
DOI: 10.1088/1755-1315/921/1/012006
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Leadership Quality and Service Innovation in Public Organizations: A Conceptual Framework

Abstract: Indonesia’s public services are constantly being criticized for not proficiently attending to societal needs, despite government rules and guidelines. The regulation on regional innovation specified direction on services in the form of local governance, public support, and/or other inventions by governmental aff airs within jurisdiction. Furthermore, local governments are mandated to deliver maximum satisfaction with allotted incentives by way of rating public service innovations. However, in reality, several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Studies on the implementation of public service innovations conducted by several previous studies have identified that the successful implementation of public service innovations in Indonesia is highly dependent on leadership aspects ICHELSS [12]- [16]. Effective leadership is able to stimulate motivation which in turn encourages the implementation of innovation [13]. Effective leadership is meant by the results of previous research, namely when a leader has a reliable leadership style [16] and continues to make changes consistently and has the initiative to make breakthroughs [15].…”
Section: Resultsmentioning
confidence: 99%
“…Studies on the implementation of public service innovations conducted by several previous studies have identified that the successful implementation of public service innovations in Indonesia is highly dependent on leadership aspects ICHELSS [12]- [16]. Effective leadership is able to stimulate motivation which in turn encourages the implementation of innovation [13]. Effective leadership is meant by the results of previous research, namely when a leader has a reliable leadership style [16] and continues to make changes consistently and has the initiative to make breakthroughs [15].…”
Section: Resultsmentioning
confidence: 99%
“…The purpose of public organisations is to fulfill the public interest. it has become the duty of public organisations to provide maximum services to the community (Nurung et al, 2021). In order to achieve this maximum service, the very difficult task of public bodies is to ensure that their employees are effectively able to serve the public interest of citizens by taking full responsibility for each task they have to perform (Lim & Lee, 2021).…”
Section: Career Management In Public Administration Perspectivementioning
confidence: 99%